Computational Nonlinear Thermomechanical Model of Large Light Partition Walls Based on Experimental Analysis and Probabilistic Models. (8th November 2012) - Do, T. T.; Soize, C.; Heck, J.‐V.
<x xml:space="preserve">Abstract</x> Abstract: This article is devoted to the construction of a computational nonlinear thermomechanical model of large light partition walls made up of cardboard‐plasterboard‐cardboard (CPC) plates screwed to a metallic frame, and is submitted to mechanical and thermal loadings induced by fire. The computational model, based on experimental analysis and a probabilistic modeling, is developed for the prediction of a large light partition wall for (1) its linear thermal behavior, (2) its nonlinear mechanical behavior, and (3) its nonlinear thermomechanical behavior.